Orthogonal excitations of lanthanide nanoparticle up/down conversion emissions via switching NIR lights for in-vivo theranostics. (December 2022) - Zhao, Hongxia; Li, Yuetong; Zhang, Xiaobo; Wu, Kun; Lv, Jiahang; Chen, Cheng; Liu, Huipu; Shi, Zhuangzhi; Ju, Huangxian; Liu, Ying
Abstract : With multiple emissions ranging from NIR-IIb to visible lights, near-infrared light-excited lanthanide nanoparticle (LnNP) is an ideal in-vivo theranostic platform to achieve imaging guided phototherapy. However, current reported LnNPs typically demonstrate simultaneous up and downconversion emissions with fixed single excitation light, which impairs therapeutic efficiency and generates side effect during navigation. Here we develop a lanthanide-based conversion switching nanoparticle (CSNP) with independent activation of 1550 nm NIR-IIb downconversion emission under 808 nm excitation and 345/450 nm upconversion emission under 980 nm excitation. CSNP is modified with Cy-GSH to quench NIR-IIb emission and photosensitizer hypocrellin A. In vivo delivery of CSNP is traced via 808 nm irradiation, and Cy-GSH changes structure in response to glutathione to activate NIR–IIb imaging. This indicates the tumor position and timing to switch for 980 nm irradiation to activate hypocrellin A for photodynamic therapy. Orthogonal activation of CSNP up/down conversion emissions demonstrates high tumor-to-normal tissue ratio in vivo and good therapeutic result, would have promising potential as a theranostics platform.